2023
DOI: 10.3390/met13091610
|View full text |Cite
|
Sign up to set email alerts
|

Long Sump Life Effects of a Naturally Aged Bio-Ester Oil Emulsion on Tool Wear in Finish Turning a Ni-Based Superalloy

Paul Wood,
Andrew Mantle,
Fathi Boud
et al.

Abstract: This paper discusses a method of finish turning Inconel 718 alloy to compare machining performance of a naturally aged and used metalworking fluid (MWF), which had been conventionally managed through its life cycle, with the same new unaged product. The MWF concentrate was a new-to-market bio-ester oil, diluted with water to produce an emulsion. In the experiments, 50 mm diameter bars were turned down with multiple passes at a 250 μm depth of cut to reach a tool flank wear of 200 μm. The machining was interrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 39 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…Whilst some key performance measures in these published articles were studied, such as tool wear or surface integrity, none considered the broader range of performance measures covering, for example, tool wear rate, cutting forces, chip forms, surface and subsurface integrity in the performance evaluation of the CF to finish turn this alloy. This paper complements the recent work [24] that studied the effect of a long sump life of a bio-ester emulsion on tool wear in finish turning a Ni-based superalloy. Furthermore, the number of performance measures was increased to compare the bio-ester and mineral-oil-based emulsions with the aim of increasing confidence in the findings.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Whilst some key performance measures in these published articles were studied, such as tool wear or surface integrity, none considered the broader range of performance measures covering, for example, tool wear rate, cutting forces, chip forms, surface and subsurface integrity in the performance evaluation of the CF to finish turn this alloy. This paper complements the recent work [24] that studied the effect of a long sump life of a bio-ester emulsion on tool wear in finish turning a Ni-based superalloy. Furthermore, the number of performance measures was increased to compare the bio-ester and mineral-oil-based emulsions with the aim of increasing confidence in the findings.…”
Section: Introductionsupporting
confidence: 64%
“…The cause of notch wear was attributed to high surface work hardening of the workpiece in the chip-forming region that developed a high adiabatic temperature. Wood et al [24] identified significant notching when flank wear exceeded 0.3 mm in finish turning Inconel 718. Darshan et al [44] found different CFs, and their application methods influenced the chip forms that were attributed to the prevailing friction conditions.…”
Section: Tool Wear Failure Modes In Turning Inconel 718mentioning
confidence: 99%
See 3 more Smart Citations